2013
DOI: 10.1080/13803395.2013.815693
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorder in childhood impairs declarative but not nondeclarative forms of learning

Abstract: A large amount of studies have investigated the association between sleep and memory systems. However, remarkably little is known of the effect of sleep disorders on declarative and nondeclarative memory for children. In the present study we examined the effects of sleep disorders on different aspects of memory functions by testing children with sleep-disordered breathing (SDB), which is characterized by disrupted sleep patterns. We used "The War of the Ghosts" test to measure declarative memory and the Altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 66 publications
9
27
0
1
Order By: Relevance
“…We found that these two types of non-declarative learning and consolidation are intact in children with SDB. Our results on online declarative memory performance are in line with previous studies that found weaker declarative performance in the SDB group in general Csábi et al, 2013). found lower performance on verbal and visual memory tasks in children with SDB compared to healthy controls.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…We found that these two types of non-declarative learning and consolidation are intact in children with SDB. Our results on online declarative memory performance are in line with previous studies that found weaker declarative performance in the SDB group in general Csábi et al, 2013). found lower performance on verbal and visual memory tasks in children with SDB compared to healthy controls.…”
Section: Discussionsupporting
confidence: 83%
“…Our results are in line with our previous study in which the SDB group showed impaired declarative memory performance while the non-declarative learning remained intact compared to the healthy controls (Csábi et al, 2013). using the ASRT task also found intact non-declarative sequence learning in elderly adults with OSA.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations